Thermal tuning of protein hydration in a hyperthermophilic enzyme - Fusco, Giuliana; Biancaniello, Carmen; Vrettas, Michail D.; De Simone, Alfonso (Frontiers in Molecular Biosciences, 2022)
Water at the protein surface is an active biological molecule that plays a critical role in many functional processes. Using NMR-restrained MD simulations, we here addressed how protein hydration is tuned at high biological temperatures by analysing homologous acylphosphatase enzymes (AcP) possessing similar structure and dynamics under very different thermal conditions. We found that the hyperthemophilic Sso AcP at 80 °C interacts with a lower number of structured waters in the first hydration shell than its human homologous mt AcP at 37 °C. Overall, the structural and dynamical properties of waters at the surface of the two enzymes resulted similar in the first hydration shell, including solvent molecules residing in the active site. By contrast the dynamical content of water molecules in the second hydration shell was found to diverge, with higher mobility observed in Sso AcP at 80 °C. Taken together the results delineate the subtle differences in the hydration properties of mt AcP and Sso AcP, and indicate that the concept of corresponding states with equivalent dynamics in homologous mesophilic and hyperthermophylic proteins should be extended to the first hydration shell.